Mathematical modeling and simulation studies of scale-down fermentation systems - Ozbek, B (WILEY-V C H VERLAG GMBH, 1997)
In this study, a scale-down approach has been used for the simulation of the imperfect mixing on the growth processes by considering several configurations of continuous stirred tank reactor (CSTR, aerated) and plug flow tubular reactor (PFTR, not aerated). The steady-state concentrations of biomass and enzyme in a continuous culture were calculated as a function of dilution rate using modified Monod growth kinetics. A mathematical model for each combination of two bioreactors was developed to account for growth, substrate utilization (oxygen and glucose) and enzyme synthesis and decay. The model was then used to investigate biomass production and enzyme expression in relation to the volumetric fraction upsilon(f) = V-PFTR/(V-CSTR+ V-PFTR) and the recirculation ratio R =f(r)/(f+f(r)) of the fermentation system. These two mixing parameters were found to be significant factors in the biomass and enzyme production from the fermentation system. This model was also compared with some of the existing models.
Keywords: Engineering